Pengaruh Ulasan Online, Kepercayaan Merek dan Kepuasan Pelanggan terhadap Niat Pembelian Ulang Ms Glow di Batam - Sirait, Bayu Febryanti; Evyanto, Winda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study investigates the influence of online reviews, brand trust, and customer satisfaction on consumer’s repurchase intention for MS Glow skincare products in Batam, Indonesia. The growing prevalence of digital platforms has transformed how consumers evaluate products, with online feedback increasingly shaping purchase decisions. However, concerns remain regarding the reliability of user-generated reviews, brand credibility, and product satisfaction, which may affect customer loyalty and repeat purchases. Using a quantitative approach with a descriptive research design, this study surveyed 100 individuals who had previously purchased MS Glow products. Respondents were selected using purposive sampling based on Lemeshow’s framework. Data were collected through a structured questionnaire tested for validity and reliability, and analyzed using multiple statistical tools including classical assumption tests, multiple linear regression, and both t- and F-tests. The results show that online reviews have the most significant impact on repurchase intention, contributing 60.1%, followed by brand trust at 13.5% and customer satisfaction at 11.9%. Together, these three variables account for 87.0% of the variance in repurchase intention. Each variable also showed a significant and positive individual effect. These findings highlight the critical role of digital reputation, trust-building, and post-purchase satisfaction in sustaining customer loyalty. It is recommended that MS Glow continuously monitor consumer feedback, ensure transparent communication, and maintain product consistency to foster stronger repurchase behavior among its consumers.